Improving soil properties to prevent surficial slope failure - Daneshmand, Saman (2009)
Many hill slope areas in Malaysia are vulnerable to soil erosion and shallow slope failures due to intense and frequent rainfall events. Rainfall induced slope failure can be attributed to: seepage force and seepage erosion, the loss of shear strength of the soil, and formation of tension cracks. Lime was used to improve soil properties and resistance against failure. When mixed with in-situ soil, the lime can reduce the potential for swelling and shrinkage; therefore inhibit the formation of cracks at the surface. Lime can also reduce the soil’s dispersibility, therefore reduce the erosion potential. Soil mixed with lime has lower permeability, therefore enhance of capillary barrier effect and limit the rainfall infiltration into the soil. This study focuses on the improvement of soil properties to prevent surficial slope failure. Laboratory tests have been performed on soil and soil mix with deferent percentage of lime to evaluate properties of blended soil. The results show that the optimum lime content to be used in the mix design is 7%. A two dimensional finite element model of the slope was used to evaluate the performance of the optimum lime – soil mix as capillary barrier. The analysis revealed that the optimum thickness of slope cover system as capillary barrier is 30cm.